Math on call : a mathematics handbook. (Wilmington, MA : Great Source, 1998)
A math resource book featuring definitions, procedures, explanations, and rules for topics in numeration, number theory, computation, algebra, graphs and statistics, geometry, ratio, proportion, percents, probability, and odds. Includes a selection of reference aids.
Includes index.
Young Adult
Keywords: Mathematics; Mathematics -- Problems, exercises, etc; Mathematics; Mathematics -- Problems, exercises, etc